(untitled) (Journal of the College of Basic Education, 2024)
The research aims to identify the effect of teaching mathematics using the Wheel of Inquiry model on the achievement and information generation skills of fifth grade primary school students. The Irbid Primary Mixed School affiliated with the General Directorate of Education of Baghdad/Al-Rusafa 1 was chosen randomly. The research sample consisted of (56) male and female students from the fifth grade of primary school in the first semester of the academic year (2023-2024) AD, and Division (B) was randomly chosen to be the group. The experimental group was studied according to the wheel of inquiry model, and section (C) was the control group that was studied according to the usual method, with (28) male and female students for each of the two research groups. The two groups were rewarded with the variables: (intelligence, chronological age in months, and previous knowledge in the subject Mathematics, and the educational level of the parents). The test for information generation skills in mathematics was prepared according to three skills (inference, prediction, expansion), consisting of (16) paragraphs (objective, multiple-choice type) with (6) inference items including three paragraphs. Deductive, three inductive paragraphs, (5) prediction paragraphs, and (5) expansion paragraphs, and using the Keuder-Richardson equation (KR-20), the value of the reliability coefficient was 0.83). After completing the experiment, the test and skills of generating information in mathematics was applied to the two research groups, and the statistical program was used. (spss) to process the data obtained and the results showed that there was a significant difference between the average scores of the two research groups (control and experimental) in the information generation skills test and in favor of the experimental group according to the teaching method.